Reproducibility of technetium-99m mercaptoacetyltriglycine clearance in patients with impaired renal function - ÖNEŞ, TUNÇ; TUĞLULAR, ZÜBEYDE SERHAN (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Background The aim of this study was to determine the reproducibility of technetium-99m mercaptoacetyltriglycine ((99)mTc-MAG3) clearance in patients with a 99mTc-MAG3 clearance below 100 ml/min/1.73 m(2). Methods Two separate multi-sample clearance studies were performed in 16 patients at a 1 week interval. The clearances were calculated according to the open two-compartment model of Sapirstein et al., accepting the 90, 120 and 180 min samples as the last points of the biexponential curve. The clearance measurements were also performed according to the single-sample methods of Russell et al. and Bubeck using the fitted value at 44 min. Results There was no significant difference between the two clearance measurements for all five samples (P > 0.05). There was a systematic increase in clearance measurements of 8.0 +/- 2.7% from the 180 to 120 min samples and 4.8 +/- 2.0% from the 120 to 90 min samples. Both single-sample methods (Bubeck and Russell et al.) gave more divergent results than multi-sample methods. The mean and standard deviation (%) of the normalized differences between two successive tests were -3.9 +/- 12.6, -2.4 +/- 13.1, -1.9 +/- 14.9, -4.1 +/- 53.5 and -13 +/- 82.1 for 90,120 and 180min samples and the Russell et al. and Bubeck methods, respectively. Conclusion Single-sample methods give very poor reproducibility and accuracy and should not be used in patients with poor renal function. The reproducibility of Tc-99m-MAG3 clearance using the multi-sample method (90 min) in patients with impaired renal function is 12.6%, which is similar to that in patients with good renal function and that obtained with other tubular agents. Whether this level of reproducibility is satisfactory for documenting serial changes in an individual patient with a Tc-99m-MAG3 clearance below 100 ml/min/1.73 m(2) depends on the expectation of the clinician.
Keywords: clearance; impaired renal function; reproducibility; Tc-99m-MAG3; GLOMERULAR-FILTRATION RATE; TECHNETIUM-99M MAG3; SINGLE-INJECTION; TC-99(M)-MAG3 CLEARANCE; NORMAL VOLUNTEERS; PLASMA-CLEARANCE; SAMPLE; RADIONUCLIDES; ACCURACY; CHILDREN